Development of fun flashcard series: Fruits and animals for primary students for children at Mustika Tama Orphanage - Yunita Miftahul Jannah; Fransiskus Ransus; Verawaty Sinaga; Agrielsa Alphasati Sinaga; Ratih Kusumo Wardani (Priviet Social Sciences Journal, 2025)
This study aims to develop the Fun Flashcard Series: Fruits & Animals learning media as an educational tool to increase the learning motivation and involvement of children at Mustika Tama Orphanage. The development model used was 4D (Define, Design, Develop, Disseminate). The research subjects were 10 children in grades 1 and 2 at the elementary school level at the Mustika Tama Orphanage. The research instruments included expert validation sheets, child response questionnaires, and learning engagement observation forms. The validation results showed that the Fun Flashcard Series media was very suitable for use, with an average validation score of 95%. The children's responses showed a high level of enthusiasm, engagement, and interest in the developed media. Thus, the Fun Flashcard Series: Fruits & Animals proved to be effective as an innovative learning medium that can increase children's learning motivation and engagement at the Mustika Tama Orphanage.